The Role of Digitalization in the Era of Society 5.0 on MSME Performance - Roshaliya, Defi; Inayati, Nur Isna; Wahyuni, Sri; Hapsari, Ira (Yayasan Sinergi Kawula Muda, 2025)
This study aims to analyze the effect of digital accounting, digital organization, and media capability on MSME performance. This study uses quantitative research methods. The population of this study consisted of Micro, Small, and Medium Enterprises (MSMEs) registered with the Banyumas Regency Micro, Small, and Medium Entrepreneurs Association (ASPIKMAS). The sampling technique used was purposive sampling, which was taken as many as 106 respondents. This study used a quantitative approach to achieve these objectives by collecting primary data through distributing questionnaires. The analysis used the Structural Equation Model (SEM) with the Partial Least Square (PLS) approach. Based on the research results, it is concluded that digital accounting has a positive and significant influence on the performance of MSMEs. Second, digital organization has a positive and significant influence on the performance of MSMEs. Third, media capability also has a positive and significant influence on the performance of MSMEs.